2019
DOI: 10.3390/app9112356
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rolling Bearing Fault Diagnosis and Severity Analysis Method

Abstract: To improve the fault identification accuracy of rolling bearing and effectively analyze the fault severity, a novel rolling bearing fault diagnosis and severity analysis method based on the fast sample entropy, the wavelet packet energy entropy, and a multiclass relevance vector machine is proposed in this paper. A fast sample entropy calculation method based on a kd tree is adopted to improve the real-time performance of fault detection in this paper. In view of the non-linearity and non-stationarity of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…At the same time, it can be found that, in the nodes [2,0], the energy difference is almost zero, which is the same as in the first layer of nodes [1,0]. Although the energy difference of nodes [2,3] fluctuates, it does not exceed the set threshold, so it is considered that the change is mainly caused by the noise contained in the data. In Figure 12, node [3,0] and node [1,0] have no fault data as in [2,0].…”
Section: Improved Mspca Fault Data Recognition Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…At the same time, it can be found that, in the nodes [2,0], the energy difference is almost zero, which is the same as in the first layer of nodes [1,0]. Although the energy difference of nodes [2,3] fluctuates, it does not exceed the set threshold, so it is considered that the change is mainly caused by the noise contained in the data. In Figure 12, node [3,0] and node [1,0] have no fault data as in [2,0].…”
Section: Improved Mspca Fault Data Recognition Resultsmentioning
confidence: 91%
“…In Figure 11, the energy of wavelet packet of node [2,1] detects data faults at about 225-275 data points, and the range of data faults detected by node [2,2] is about 200-275, 300-350 data points. In the nodes [2,0] and [2,3], there is no fault information. At the same time, it can be found that, in the nodes [2,0], the energy difference is almost zero, which is the same as in the first layer of nodes [1,0].…”
Section: Improved Mspca Fault Data Recognition Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The failures of rolling bearings often develop from the normal stage to the incipient stage, then enter the stage of repeated failure, and finally reach the stage of complete breakdown. The serious faults do not occur in an instant, but has a process of gradual deterioration [5][6][7]. Therefore, it is of great significance to study the incipient fault detection of rolling bearings, find the incipient signal characteristics of faults, and eliminate the safety hazards in time when the fault has not developed toward a serious degree [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the importance of bearing fault severity recognition has been paid more and more attention [2,3]. In general, the damage severity of bearings is usually measured from the aspect of signal complexity [4].…”
Section: Introductionmentioning
confidence: 99%